Deformation Analysis of Self-Expanding Stent Considering Plaque and a New Expanding Mechanism - Katsuhiko Sasaki; Yukiko Tomooka; Ryo Takeda; Achmad Syaifudin (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2018)
In this research, effects of material properties of stent materials, such as nitinol and ferrous alloy, on a self-expanding stent are studied by the stent deployment simulations using finite element method (FEM). Stent, vessel, and plaque are modeled by using AutoCAD. The model is imported to a finite element analysis software Ansys 15.0 and the deployment analysis of the stent is carried out. In addition, two methods of the unsheathing of the self-expanding stent are studied: (1) a conventional method where a stent comes out from one end of the sheath and (2) a new method in which a stent comes out from the center of the sheath. Also, both the area stenosis ratio and Dog-Boning are discussed referring the simulations conducted in the paper.